Epidemiological shift and clinical characteristics of rhinovirus genotypes in acute respiratory tract infection cases in Kunming, China, from 2019 to 2023 - Zhang, Guiqian; Ba, Limei; Liu, Luping; Su, Ting; Zhu, Hongyan; Xu, Ya; Zhang, Yufan; Huang, Yafei; Fan, Xin; Wan, Jinxiu; Gao, Jianmei; Li, Hailong; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundWe aimed to investigate the impact of the coronavirus disease 2019 (COVID-19) outbreak on the genetic diversity and clinical severity of rhinovirus (RV) in acute respiratory tract infection (ARTI) cases in Kunming, China.MethodsA total of 25,769 patients with ARTI from September 1, 2019 to December 31, 2023 were enrolled. Patients with COVID-19 were excluded from the study. Nasopharyngeal swabs were collected and screened for RV using multiplex reverse transcription polymerase chain reaction. RV-positive samples underwent nested PCR targeting the VP4/VP2 region. The amplified products were sequenced for genotype identification.ResultsA total of 1,017 RV-positive cases were identified (detection rate 3.95%; 1,017/25,769), and all three RV species—RV-A, RV-B, and RV-C—were detected; RV-A was the most prevalent. Overall, 128 distinct RV genotypes, 40 untyped strains, and 1 recombinant strain (A1B) were identified. The predominant genotypes differed between age groups: those <18 years were mainly infected with C-untyped, A36, and A12, whereas those ≥18 years had C1, B52, and A60. Among RV-positive cases, 42.97% were associated with lower respiratory tract infections (LRTI), mainly caused by RV-A and RV-C. RV-C was associated with higher C-reactive protein and procalcitonin. Co-occurrences were recorded in 24.98% (254/1,017) of RV-positive cases and were associated with prolonged hospitalization. RV exhibited no clear seasonal pattern; however, following the COVID-19 outbreak, RV-C was replaced by RV-A.ConclusionsRV remains endemic with significant genetic diversity in the region. The COVID-19 pandemic led to a notable shift in the dominant circulating species from RV-A to RV-C. Emerging mutant strains have contributed to increased disease severity. Both RV-C and RV-A contribute to LRTI in children.